A call to mission : the Jesuits in China, 1842-1954. - Strong, David, 1939- (ATF Theology, 2018)
"China has bulked large in the imagination of the Catholic Church for 500 years. It had been central to the missionary dream of the Jesuits for almost as long. However, only with this book's appearance has the detailed focus of attention shifted to the substantial and neglected period of catholic and Jesuit engagement with China -- the almost 120 years from the second arrival of the Jesuits. Volume 1: The French Romance traces the people, projects, expansion and impact of those who provided the predominant Jesuit presence. At the height of its engagement with China, the French Government had 19 Consulates and attendant military and navy throughout China. The French Jesuits were afforded access and protection by their government and activated missions in northern and central China -- schools, seminaries, universities, parishes, retreat houses, publications -- and attracted Chinese nationals to join their number."--